Estimating Demand for Third-party Quality Testing in Rural Grain Markets: Evidence from an Experimental Auction for Measuring Moisture Content in Kenya. (2nd March 2021) - Fuller, Amanda J; Ricker-Gilbert, Jacob
Abstract: Traders in informal grain markets often lack incentives to sell grain dried to a moisture level that is safe for storage, due to weak regulations and lack of low-cost moisture testing technologies. This study estimated the demand for a third-party moisture testing service in western Kenya that can encourage safe drying and reduce asymmetric information between buyers and sellers. We utilised a Becker–DeGroot–Marschak (BDM) auction to obtain maize traders' willingness to pay (WTP) for the moisture testing service and compared it with two alternative multiple price list (MPL) mechanisms for eliciting WTP. Traders had the opportunity to bid on the testing service with two different moisture metres. The first was a low-cost hygrometer that measures temperature and relative humidity and costs about $2.50. The second was a commercial moisture metre that costs $170 in USA but provides a more precise reading. Results suggest that the standard BDM auction and both MPL variants produced similar estimates of demand for our moisture testing service. On average, traders were willing to pay $0.28 to have their maize tested with the hygrometer and $0.39 with the moisture metre. An additional take-it-or-leave-it auction for the hygrometer itself revealed that traders were not sensitive to price changes around market price, although only 15% of the traders purchased the device. A service provider model using either device could be a way to make moisture testing accessible in rural grain markets in the absence of a supply chain that sells these devices directly.